ANALISIS PENGARUH LEADER’S EMOTION TERHADAP JOB PERFORMANCE DENGAN POWER DISTANCE DAN TASK INTERDEPENDENCE SEBAGAI VARIABEL MODERATOR (Studi pada BAPPEDA Provinsi Jawa Tengah) - Lestari, Fitri Wahyu; Suharnomo, Suharnomo (Faculty of Economics and Business Diponegoro University, 2017)
The achievement of a organization goals is influenced by various factors, one of it is performance. The performance reflects how well employees are meeting their targets in a job. This study aims to determine the influence of leader’s emotion towards employee performance with power distance and task interdependence as a moderation variable.This research was conducted to employees of BAPPEDA Central Java Province with the number of samples by 105 respondents. Data was collected using these three methods which are interviews, questionnaires and literature studies. Simple regression analysis and moderated regression analysis was used in order to conduct this study.The results of this studies are: Leader’s Emotion affect positively towards the employees performance, Power Distance attenuated the positive relationship between the leader's emotion and the employee's job performance and, Task Interdependence attenuated the positive relationship between the leader's emotions and employee’s job performance.